Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1103/physrevlett.98.083001
|View full text |Cite
|
Sign up to set email alerts
|

Control of Molecular Energy Redistribution Pathways via Surface Plasmon Gating

Abstract: Strong coupling of molecular electronic states with tunable surface plasmon resonances is used to control electronic energy redistribution pathways in molecules adsorbed on a silver film. Ultrafast excitation of porphyrinic molecular J aggregates into the S2 state is followed by a second pulse of varying incident wave vector to produce a tunable plasmon in the film. When the plasmon overlaps the S1 state, energy flows from S2 to S1 at high efficiency. If the plasmon hybridizes with the S2 state, the excitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 26 publications
2
68
1
Order By: Relevance
“…The interaction between plasmon and exciton is of great fundamental interest with strong technological implications in organic electronics and photovoltaics. It has been shown that the surface plasmon can be used to control the relaxation pathways of molecular excitons [119]. Furthermore, in a fashion similar to plasmon hybridization, atomic or molecular exciton can hybridize with plasmon, forming a new quantum mechanically entity sometimes called plexciton [120,121].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between plasmon and exciton is of great fundamental interest with strong technological implications in organic electronics and photovoltaics. It has been shown that the surface plasmon can be used to control the relaxation pathways of molecular excitons [119]. Furthermore, in a fashion similar to plasmon hybridization, atomic or molecular exciton can hybridize with plasmon, forming a new quantum mechanically entity sometimes called plexciton [120,121].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these clear and consistent observations, the relaxation dynamics of the polaritons into the noncoupled MEs, as well as scatterings among them, are still not fully understood. 25,31,32 Recent time-resolved studies have shed some light on the issue, 33,34 and have demonstrated Rabi oscillations as a clear signature of strong coupling. 35 However, at the same time there has been significant evidence about unexpectedly long lifetimes of the polaritons, 36 suggesting more pronounced scattering or maybe even thermalization among them.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems exhibit a wide variety of new phenomena including new mixed molecular-plasmon states [24] and plasmon control of molecular energy redistribution [25].…”
Section: Introductionmentioning
confidence: 99%